2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23373
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of engineering students’ creative self-concepts: An exploration of creative self-efficacy, personal identity, and expectations

Abstract: The purpose of this paper is to expand the research base on creativity by assessing engineering students' creative self-concepts. A cross-sectional study of first-year and senior engineering students was conducted to investigate three constructs that measure creative selfconcept: creative self-efficacy, creative personal identity, and creative expectations. Gender differences in how creative self-concepts differ from first-year to senior year were also explored. The results show that female students have lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In interviews with undergraduates in the United States and Australia, Cropley (2015a) found that students held the view that engineering programs are dominated by "convergent, analytical work and passive knowledge acquisition" and do not reward creativity (p. 163). Early results from a cross-sectional study of approximately 800 undergraduates in 13 engineering disciplines by Zappe, Reeves, Mena, and Litzinger (2015) similarly found that self-reported creative identity scores were statistically lower among a cohort of seniors than a different cohort of first-year students, while creative expectations were significantly much lower for seniors than for first-year students. Zappe et al (2015) suggested that students do not feel they have further developed creative capacities in the engineering curriculum and that by senior year they no longer believe that creativity is important in the engineering field.…”
Section: Creativity As a Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…In interviews with undergraduates in the United States and Australia, Cropley (2015a) found that students held the view that engineering programs are dominated by "convergent, analytical work and passive knowledge acquisition" and do not reward creativity (p. 163). Early results from a cross-sectional study of approximately 800 undergraduates in 13 engineering disciplines by Zappe, Reeves, Mena, and Litzinger (2015) similarly found that self-reported creative identity scores were statistically lower among a cohort of seniors than a different cohort of first-year students, while creative expectations were significantly much lower for seniors than for first-year students. Zappe et al (2015) suggested that students do not feel they have further developed creative capacities in the engineering curriculum and that by senior year they no longer believe that creativity is important in the engineering field.…”
Section: Creativity As a Predictormentioning
confidence: 99%
“…Early results from a cross-sectional study of approximately 800 undergraduates in 13 engineering disciplines by Zappe, Reeves, Mena, and Litzinger (2015) similarly found that self-reported creative identity scores were statistically lower among a cohort of seniors than a different cohort of first-year students, while creative expectations were significantly much lower for seniors than for first-year students. Zappe et al (2015) suggested that students do not feel they have further developed creative capacities in the engineering curriculum and that by senior year they no longer believe that creativity is important in the engineering field. They further hypothesized that in light of these results, it may be that highly creative students are no longer in the engineering cohort, and called for a study evaluating creativity and engineering student persistence.…”
Section: Creativity As a Predictormentioning
confidence: 99%
“…The importance of creativity in the teaching of engineering is an aspect which is becoming more important, although it is not yet an approach that is fully generalised (Liu & Schönwetter, 2004). Zappe et al (2015) claims that students do not perceive that they improved their creative skills in the engineering curriculum, and that they thought that creativity is important in the aim of engineering. Therefore, another workshop was held by the research group for the development of spatial skills at the University of La Laguna (http://dehaes.webs.ull.es) in the 2016-17 course (called 2016-17 Workshop in this paper) in which engineering students participated in an experiment to create digital terrain models.…”
Section: Introductionmentioning
confidence: 99%
“…Zappe et al [16] found that, in a six-year period, only 16 articles related to creativity or the creative process appeared in the top five journals on engineering education. Another author concludes that, although students consider creativity to be an important factor in engineering, they do not have the perception of having improved their creative abilities during their university studies [17]. Although interest in creative processes in engineering is growing, its implementation in the classroom is still scarce [10,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%